A Fixed Point Approach to the Stability of an Additive-Quadratic-Cubic-Quartic Type Functional Equation - Yang-Hi Lee; Soon-Mo Jung (Journal of Function Spaces)
By applying a fixed point approach, we investigate the stability problems for an AQCQ functional equation of the form fx+2y+fx-2y-4fx+y-4fx-y+6fx-f2y-f-2y+4fy+4f-y=0.